The role of EBV lytic genes in tumor development and progression - DENG Yizhang; ZHONG Qian (Guangxi Yike Daxue xuebao)
Epstein-Barr virus (EBV), the first human oncolytic virus, is the causative agent of several cancers of epithelial and lymphoid origin. The life cycle of EBV consists of two phases, the latent and lytic phases. The lytic cycle is the phase in which new virus particles are produced, whereas the latent cycle is a state of persistent infection that does not result in efficient viral replication. The current view is that latent-phase genes are key drivers of the pathogenesis of EBV-associated cancers, whereas lytic genes are primarily responsible for viral transmission. However, recent evidence suggests that the lytic phase of EBV also plays an important role in EBV tumorigenesis, and researchers have detected the expression of lytic genes in tumor tissues and cell lines. This paper will outline the contributory role of EBV lytic genes in tumorigenesis and discuss possible future research directions.